The seed of Litchi chinensis fraction ameliorates hippocampal neuronal injury in an Aβ25-35-induced Alzheimer's disease rat model via the AKT/GSK-3β pathway. (1st January 2020) - Sun, Yueshan; Wu, Anguo; Li, Xiu; Qin, Dalian; Jin, Bingjin; Liu, Jian; Tang, Yong; Wu, Jianming; Yu, Chonglin
Abstract: Context: The seed of Litchi chinensis Sonn., a famous traditional Chinese medicine, was recently reported to enhance cognitive function by inhibiting neuronal apoptosis in rats. Objective: We determined whether the seed of Litchi chinensis fraction (SLF) can ameliorate hippocampal neuronal injury via the AKT/GSK-3β pathway. Materials and methods: We established Alzheimer's disease (AD) model by infusing Aβ25-35 into the lateral ventricle of Sprague–Dawley (SD) rats and randomly divided into five groups ( n = 10): sham, donepezil and SLF (120, 240 and 480 mg/kg/d). Rats were treated by intragastric administration for 28 consecutive days. Spatial learning and memory were evaluated with Morris water maze, while protein expression of AKT, GSK-3β and tau in the hippocampal neurons was measured by Western blotting and immunohistochemistry. Results: On the fifth day, escape latency of the AD model group was 45.78 ± 2.52 s and that of the sham operative group was 15.98 ± 2.32 s. SLF could improve cognitive functions by increasing the number of rats that crossed the platform ( p < 0.01), and their platform quadrant dwell time ( p < 0.05). The protein expression level of AKT was upregulated ( p < 0.001), while that of GSK-3β and tau ( p < 0.01) was remarkably downregulated in the hippocampal CA1 area. Discussion and conclusions: To our knowledge, the present study is the first to show that SLF may exert neuroprotective effect in AD rats via the AKT/GSK-3β signalling pathway, thereby serving as evidence for the potential utility of SLF as an effective drug against AD.